A randomised controlled trial of effectiveness and safety of Niclosamide as add on therapy to the standard of care measures in COVID-19 management. (September 2021) - Abdulamir, Ahmed S.; Gorial, Faiq I.; Saadi, Sattar Jabar; Maulood, Mohammed Fauzi; Hashim, Hashim Ali; Alnuaimi, Ahmed Sameer; abdulrrazaq, Manal K.
Abstract: Background: COVID-19 pandemic has ignited the urge for repurposing old drugs as candidate antiviral medicines to treat novel challenges of viral infections. Niclosamide (NCS) is an anti-parasitic drug of known antiviral potential. Therefore, this study attempts to investigate the antiviral effect and safety of NCS on SARS-CoV-2 caused COVID-19 patients. Methods: Randomized controlled open label clinical trial encompassed 75 COVID-19 patients treated with standard of care plus NCS were included as experimental group and 75 COVID-19 patients treated with only standard of care therapy as control group. Survival rate, time to recovery, and side effects were the main endpoints for the assessment of the therapeutic effect and safety of NCS. Results: No significant difference between the two study groups in the incidence of death Vs recovery within 30 days of follow up(p = 1).Median survival time to cure in the NCS addon group was significantly less than controls (5 Vs 7days, Log rank p = 0.005).All the recoveries took place within 20 days in the NCS add on group, which is 10 days shorter than that in the controls (30 days), NCS add on treatment increased the risk of cure by 60% per day compared to control group (adjusted HR = 1.6, p = 0, 007) after adjusting for the count of comorbidities. Additionally, two or more comorbidities reduced the risk of cure to 33% (p < 0.001).Male gender increased the risk of cure by 42% (p = 0.046). Older age group decreased the risk of recovery per day to 0.58 and 0.53 for 50–59 and 60+ years of age. Hyypertension (HT) and diabetes mellitus (DM) significantly reduced the risk of being cured per day to 0.56 (p = 0.003)and 0.65 (p = 0.039) respectively. No significant signals of safety in NCS add on therapy compared to control group. Conclusion: adding NCS to the standards of care measures increased the risk of the cure and had shorter time to stay in the hospital compared with controls., male gender increased the risk of cure, while older patients>40 years, HT, and DM decreased the risk of cure. Also, NCS add on therapy was relatively safe; hence, NCS is of clinical benefit for freeing hospital beds for more patients in pandemic crisis. Highlights: Add on use of Niclosamide (NCS) to the standards of care measures increased risk of cure. NCS add on theapy had shorter time to stay in the hospital compared to controls. NCS add on was relatively safe regimen.